KONTRIBUSI LAYANAN PERPUSTAKAAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA - Riri Tri Yulandari; Hanesman Hanesman (Universitas Negeri Padang, 2019)
This research is motivated by the problem of less optimal learning outcomes in DLE subjects in grade X Audio Video Engineering of SMK 1 Koto XI Tarusan, where 51.42% of students get learning outcomes below the Minimum Competency Standards (SKM). The purpose of this study is to reveal the extent of library services and learning motivation towards learning outcomes of DLE subjects in SMK 1 students Koto XI Tarusan 2018/2019 academic year. This research is a descriptive correlational study. The results of the data analysis showed that library services and learning motivation together contributed 25.70% to student learning outcomes in SMK 1 Koto XI Tarusan, library services contributed 69.55% to student learning outcomes in SMK 1 Koto XI Tarusan, Motivation learning contributed 16.32% to student learning outcomes in SMK 1 Koto XI Tarusan. So it can be concluded that library services and motivation to learn contribute to learning outcomes. The more optimal library services and the higher motivation to learn, the more optimal learning outcomes will be. Keywords: Library Services, Learning Motivation, Learning Outcome,